Manipulating vibratory devices' orientation and position enhances proprioceptive disturbance during upright stance. (2nd April 2016) - Pereira, Marcelo P.; Pelicioni, Paulo H. S.; Gobbi, Lilian T. B.
Abstract: We tested local vibration effects during upright standing considering: (i) the orientation of vibratory devices in relation to muscle fibres; (ii) the muscle region stimulated; and (iii) the number of stimulation spots. Results showed a higher balance disturbance with vibration devices oriented parallel to triceps surae muscle fibres. The single stimulation of the proximal region of the tibialis anterior muscle belly induces the same proprioceptive disturbance as stimulating multiple regions simultaneously.